1919
DOI: 10.1001/archinte.1919.00090220080006
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Fasting and Various Diets on the Liver Injury Effected by Chloroform Anesthesia

Abstract: Delayed chloroform injury has been reported occasionally since about 1850, sometimes diagnosed correctly, often called a postoperation acidosis or toxemia of unknown etiology ; sometimes called acute yellow atrophy when necropsy material was available. Experimental From

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

1920
1920
1942
1942

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…It has been reported that high dietary fat enhances the deleterious effect of various hepatotoxins (7)(8)(9)(10)(11)(12) or may produce cirrhosis (19,20). The present studies indicate that certain fats such as lard and cod liver oil, when fed as 25 per cent of the diet, have some protective effect against liver damage caused by excess cystine, while butter does not.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…It has been reported that high dietary fat enhances the deleterious effect of various hepatotoxins (7)(8)(9)(10)(11)(12) or may produce cirrhosis (19,20). The present studies indicate that certain fats such as lard and cod liver oil, when fed as 25 per cent of the diet, have some protective effect against liver damage caused by excess cystine, while butter does not.…”
Section: Discussionsupporting
confidence: 54%
“…Most of the reported studies state that protein (8)(9)(10)(11)(12) and yeast (14) are protective against certain liver poisons. In the present experiments, liver damage resulting from 10 per cent cystine in low fat diets was not influenced by 5 or 40 per cent casein or by 5 or 20 per cent brewer's yeast.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis would satisfactorily account for the reported failure to obtain protection from injury by chloroform when glucose is administered during the anesthesia (4).…”
Section: Methodsmentioning
confidence: 85%
“…Fasting also intensifies to a great degree the susceptibility of the hepatic cells to injury by chloroform, comparable to (4), or exceeding (5) that which results from a high fat intake.…”
mentioning
confidence: 97%
“…It has been known that starvation renders the liver more vulnerable to injury by hepatotoxins (9). Lack of certain food factors contained in yeast are said to cause fatty changes in the liver (10) and impaired function (11).…”
mentioning
confidence: 99%